Baboon thanatology: responses of filial and non-filial group members to infants' corpses. Issue 3 (11th March 2020) - Carter, Alecia J.; Baniel, Alice; Cowlishaw, Guy; Huchard, Elise
Abstract : What do animals know of death? What can animals' responses to death tell us about the evolution of species' minds, and the origins of humans' awareness of death and dying? A recent surge in interest in comparative thanatology may provide beginnings of answers to these questions. Here, we add to the comparative thanatology literature by reporting 12 cases of group members' responses to infants' deaths, including 1 miscarriage and 2 stillbirths, recorded over 13 years in wild Namibian chacma baboons. Wild baboons' responses to dead infants were similar to other primates: in general, the mother of the infant carried the infants' corpse for varying lengths of time (less than 1 h to 10 days) and tended to groom the corpses frequently, though, as in other studies, considerable individual differences were observed. However, we have not yet observed any corpse carriage of very long duration (i.e. greater than 20 days), which, though rare, occurs in other Old World monkeys and chimpanzees. We hypothesize this is due to the costs of carrying the corpse over the greater daily distances travelled by the Tsaobis baboons. Additionally, in contrast to other case reports, we observed male friends' 'protection' of the infant corpse on three occasions. We discuss the implications of these reports for current questions in the field.